1999
DOI: 10.1016/s0377-1237(17)30363-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Etiology of Respiratory Distress in Newborn

Abstract: Screening of 1986 consecutive Dve births was done for evidence of Respiratory Distress by administering Downe's scoring in a prospective study at level n nursery of a medical coUege. A detaUed antenatal, natal and postnatal history along with detaUed examination supported by relevant investigations was carried out to arrive at the etiological diagnosis of Respiratory Distress Syndrome (RDS).Results: 48 newborns developed RDS during the observation period. The incidence of RDS was 2.42%. Out of these 40.4% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 4 publications
5
19
2
Order By: Relevance
“…However, in the study done by C. Dani et al [16] it was observed that there is no significant association with respiratory distress and the sex of the baby. Similar findings were observed by Nagendra K et al, [13] who also concluded that there is no significant difference in neonatal respiratory distress in male and female neonates.…”
Section: Newborn Sexsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in the study done by C. Dani et al [16] it was observed that there is no significant association with respiratory distress and the sex of the baby. Similar findings were observed by Nagendra K et al, [13] who also concluded that there is no significant difference in neonatal respiratory distress in male and female neonates.…”
Section: Newborn Sexsupporting
confidence: 89%
“…[12] Similarly, Nagendra K et al also showed that the commonest cause for respiratory distress in neonates was RDS (18.8%) followed by TTNB (14%) and MAS (12.5%). ] 13] However, in the study done by Guyon G et al, commonest cause of distress in newborns was TTN (72%) followed by MAS (61%) and RDS (38%). [14] This could be due to enrolment of relatively more cases of preterms and less number of babies delivered by caesarean section resulting in less number of babies with RD due to TTN in our study.…”
Section: Discussionmentioning
confidence: 93%
“…However, in a study by C. Dani, 8 it was observed that there is no significant association with respiratory distress and the sex of the baby. Similar observations were observed by Negendra K. 16 who also concluded that there is no significant difference in neonatal respiratory distress in male and female neonates.…”
Section: Foetal Risk Factorssupporting
confidence: 87%
“…14 Similarly Nagendra et al also observed that the commonest cause for respiratory distress in neonates was RDS (18.8%) followed by TTNB (14%) and MAS (12.5%). 15 This variability in the present study was due to increased number of term babies in the study and referral cases with meconium stained liquor.…”
Section: Etiology and Diagnosismentioning
confidence: 70%